Climate Conditions on the Tibetan Plateau During the Last Glacial Maximum and Implications for the Survival of Paleolithic Foragers - Liu, Xiangjun; Cong, Lu; Li, Xiangzhong; Madsen, David; Wang, Yixuan; Liu, Yonggang; Peng, Jun (Frontiers in Earth Science, 2020)
Environmental conditions on the Tibetan Plateau (TP) during the last glacial maximum (LGM) are poorly known. Existing studies of environmental proxies and climate model simulations are contradictory, with interpretations varying between cold-dry and cold-wet environmental conditions which differentially influenced lake volumes, loess deposition and vegetation communities across the TP. Genetic and archaeological studies suggest anatomically modern paleolithic foragers initially occupied the TP between 60-30 ka, and may have seasonally occupied the TP during the LGM. Hence, a better understanding for LGM environmental conditions is needed in order to estimate whether paleolithic foragers could have survived on the TP during the extreme LGM cold stage. Here we report the investigation of lacustrine sediments and beach deposits within two paleoshorelines around Dagze Co on the southern TP, ~22 m and ~42 m higher than the present lake level. Optical age estimates suggest the sediments were deposited during the LGM and mid-Holocene, respectively. TraCE-21 climate model simulation results suggest that net annual LGM precipitation in the Dagze Co basin was lower than the mid-Holocene, but about the same as that of the past 1000 years. Combining the optical age estimates with TraCE-21 and CAM4 climate model simulation results, we deduce that increased summer precipitation and glacier meltwater supply, combined with decreased lake surface evaporation, produced LGM lake levels ~22 m higher than present. We also synthesized paleoenvironmental records reported across the TP spanning the LGM. This synthesis suggests that the LGM climate in the northern TP was cold and dry, but that some of the southern TP was cold and wet. These relatively wetter LGM conditions in the southern TP may have favored the growth of cold-resistant plants which, in turn, may have supported larger herbivore populations, and provided food for paleolithic foragers. We conclude that seasonal or short-term human occupation of the TP during the LGM was thus more likely in the southern TP than in the north.